Experiences to voluntarily adopt malaysian business reporting system MBRS: A case study of SMPs - Ilias A.; Ghani E.K.; Baidi N.; Azhar Z. (Sciedu Press, 2023)
The Companies Commission of Malaysia (SSM) has established the eXensible Business Reporting Language (XBRL) which is the Malaysian Business Reporting System (MBRS). This study examines the technological, organisational and environmental factors influencing the usage of MBRS among the practitioners. Using interview as the data collection among 12 respondents which are practitioners from selected Corporate Secretaries fom small medium practices (SMPs). Data from interview has analysed based on descriptive coding and pattern coding that developed by Technological, Organisational and Environmental (TOE) theory using the Atlas. ti. The findings of this study indicates seven (7) technological factors which are assurance for data quality, relative advantage and the availability of regulator's platform and system, limited tools and software, compability of format, compatibility of content and how the mTool could provide ease of use to the corporate secretary. In related to organisational factors, There are seven (7) challenges that can be considered discovered from organisational which are challenge to face attitude of preparers, limited practitioners that have own sufficient skills and knowledge, limited capable resources and preparers to manage the MBRS. In addition, there are six (6) environmental factors which are the technical support from regulator, the provision of incentive that should be given to the practitioners or SMPs, the effective strategies for promotion and educate practitioners method of voluntary submission. However, the lack of readiness on the use MBRS among trading partners and other stakeholder involvement would also challenge the adoption of MBRS. Therefore, this TOE factors would be important to practitioners to be ready on the enforcement of MBRS. 2020, Sciedu Press.